2008
DOI: 10.1016/j.rmed.2008.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Time to desaturation in the 6-min walking distance test predicts 24-hour oximetry in COPD patients with a PO2 between 60 and 70mmHg

Abstract: The time to desaturation in the 6MWD test can discriminate early desaturators who desaturate during their daily living activities and late desaturators who do not desaturate. Ambulatory oximetry would thus only be necessary in patients with a time to desaturation that ranges between 1 and 3'30''.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 26 publications
0
29
0
1
Order By: Relevance
“…11,12 In a previous study we found that early desaturation is more important than non-early desaturation. 8 The walk time to S pO 2 Ͻ 90% is also valuable information, because early versus non-early desaturation status is prognostic. Early desaturation is associated with substantial desaturation during 24-hour oximetry, which means that early desaturators might desaturate during most of their activities of daily living.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11,12 In a previous study we found that early desaturation is more important than non-early desaturation. 8 The walk time to S pO 2 Ͻ 90% is also valuable information, because early versus non-early desaturation status is prognostic. Early desaturation is associated with substantial desaturation during 24-hour oximetry, which means that early desaturators might desaturate during most of their activities of daily living.…”
Section: Discussionmentioning
confidence: 99%
“…Early desaturation is associated with substantial desaturation during 24-hour oximetry, which means that early desaturators might desaturate during most of their activities of daily living. 8 Early desaturation has true clinical importance in that early desaturators are more likely to need long-term home oxygen within 5 years, and therefore have a poorer prognosis. Our early desaturators desaturated more deeply (see Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only the patients who exhibit desaturation within the first minute of the walk test, the so-called early desaturators, also experience desaturation during their daily activities [10]. Those who desaturate past 3.5 min, the late desaturators, do not undergo desaturation in their daily life activities.…”
Section: Short Communicationmentioning
confidence: 99%
“…Garcia-Talavera et al showed that COPD patients with moderate hypoxemia at rest did not have important desaturations during daytime activities if they did not desaturate during the first 3.5 min of a 6-min walk test. 34 Predicting Which Patients May Have Exercise Desaturation. Patients with predominantly an emphysematous phenotype and a lower diffusion capacity are more likely to desaturate during exertion, compared to patients with a similar degree of air-flow obstruction but an airway predominant rather than emphysema predominant phenotype.…”
Section: Exercisementioning
confidence: 99%